2016
DOI: 10.5014/ajot.2017.023234
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Occupational Therapy Interventions for Adults With Musculoskeletal Conditions of the Forearm, Wrist, and Hand: A Systematic Review

Abstract: Occupational therapy practitioners are key health care providers for people with musculoskeletal disorders of the distal upper extremity. It is imperative that practitioners understand the most effective and efficient means for remediating impairments and supporting clients in progressing to independence in purposeful occupations. This systematic review provides an update to a previous review by summarizing articles published between 2006 and July 2014 related to the focused question, What is the evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 70 publications
2
33
0
3
Order By: Relevance
“…Because of the high percentage of PRMDs that occur in musicians, treatment may also include a biomechanical approach, including custom orthotics, modalities (e.g., heat, ultrasound), stretches, and strengthening postural and underactive muscles (Moran, 1992;Shafer-Crane, 2006). Some positive benefits of manual therapies, neural gliding, and ergonomic interventions have been found for treating clients with peripheral nerve injuries, such as carpal tunnel syndrome (Roll & Hardison, 2017). Tables 1 and 2 list specialized treatment suggestions to help occupational therapists better collaborate with musicians and address the musicians' unique concerns.…”
Section: Evaluation and Treatment Of Musiciansmentioning
confidence: 99%
“…Because of the high percentage of PRMDs that occur in musicians, treatment may also include a biomechanical approach, including custom orthotics, modalities (e.g., heat, ultrasound), stretches, and strengthening postural and underactive muscles (Moran, 1992;Shafer-Crane, 2006). Some positive benefits of manual therapies, neural gliding, and ergonomic interventions have been found for treating clients with peripheral nerve injuries, such as carpal tunnel syndrome (Roll & Hardison, 2017). Tables 1 and 2 list specialized treatment suggestions to help occupational therapists better collaborate with musicians and address the musicians' unique concerns.…”
Section: Evaluation and Treatment Of Musiciansmentioning
confidence: 99%
“…Patients with osteoporosis respond poorly to the post-immobilization physiotherapy interventions. Early activity motion is recommended for patients after fixation of distal radius fracture, surgical repair of flexor or extensor tendon injuries, and surgical tendon transfer [16].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that exercise therapy may postpone total joint replacement [ 29 ]. Physical and occupational therapy-related interventions have proven to reduce pain in patients with hand OA [ 30 , 31 ]. Additionally, self-management programs have shown to improve mental health and social connectedness, thereby improving many aspects of OA patients’ lives [ 32 – 34 ].…”
Section: Discussionmentioning
confidence: 99%